COMPARISON OF MODIFIED METHOD OF LIGATION OF INTERSPHINCTERIC FISTULA TRACT (LIFT) AND STANDARD OPERATIONS IN PATIENTS WITH TRANSSPHINCTERIC RECTAL FISTULAS - Kryvoruchko, Igor; Firsyk, Tetiana; Bozhko, Oleksandr (Inter Collegas, 2019)
COMPARISON OF MODIFIED METHOD OF LIGATION OF INTERSPHINCTERIC FISTULA TRACT (LIFT) AND STANDARD OPERATIONS IN PATIENTS WITH TRANSSPHINCTERIC RECTAL FISTULAS Kryvoruchko I.A. , Firsyk T.M.,.  Bozhko O. P. Background. The search for and development of new minimally invasive methods for the surgical treatment of anal fistulas is a relevant area of surgery. Such methods combine less traumatization and preservation of the sphincter’s complex. Employment of such methods for surgical treatment of anal fistulas reduced the time of stay of patients in the hospital and improved their quality of life. Subjects and methods. A retro- and prospective study involved 58 patients with uncomplicated transsphincteric anal fistulas. All patients were treated in the hospital from January 2014 to April 2019.  The patients were divided into two groups: the first group included 32 patients who were operated on according to the standard procedure using fistulotomy and Seton procedure; the second group consisted of 26 patients who were operated on using the modified LIFT method. Results. Most of these patients (72.4%) were men at the age of 42.536.79. The median of BMI was 25.7 kg/m2. There wasn’t mortality after operations. The median follow-up was 21 (6-48) weeks. In the first group there were 3 cases (9.3%) of anal sphincter insufficiency and 7 cases of recurrent fistulas (21.9%) at different times after surgery.  In the second group there were no anal sphincter failure following administration of the modified method LIFT, but there were 15.4% of recurrent anal fistulas. Conclusion. The proposed modified method of ligation of intersphincteric fistula tract is an effective method for the treatment of anal fistulas. The results obtained suggest that the developed method can be used to treat other types of anal fistulas. Keywords: transsphincteric anal fistula, surgical treatment, LIFT technique, postoperative complications.